1999
DOI: 10.1007/s004150050396
|View full text |Cite
|
Sign up to set email alerts
|

Antimigraine drugs

Abstract: Migraine is a paroxysmal disorder characterized by attacks of headache, nausea, vomiting, photophobia, phonophobia, and malaise. This review summarizes new treatment options for therapy of the acute attack. Mild or moderate migraine attacks are treated with antiemetics followed by analgesics such as aspirin, paracetamol, nonsteroidal anti-inflammatory drugs, or antiemetics combined with ergotamine or dihydroergotamine. Sumatriptan, a specific serotonin (5-HT)1B/D agonist is used when attacks do not respond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…32 Comparative trials have shown that 2.5 mg of naratriptan is less effective than 100 mg of sumatriptan in terms of the likelihood of achieving headache relief, but has almost no adverse effects. 45 Naratriptan has a lower headache recurrence rate than sumatriptan and rizatriptan when directly compared, but the time to recurrence is not longer with naratriptan. 29 Rizatriptan has a rapid onset of action, high bioavailability, and a favorable adverse effects profile.…”
Section: Clinical Efficacy Of the 5-ht 1b/1d Receptor Agonistsmentioning
confidence: 99%
“…32 Comparative trials have shown that 2.5 mg of naratriptan is less effective than 100 mg of sumatriptan in terms of the likelihood of achieving headache relief, but has almost no adverse effects. 45 Naratriptan has a lower headache recurrence rate than sumatriptan and rizatriptan when directly compared, but the time to recurrence is not longer with naratriptan. 29 Rizatriptan has a rapid onset of action, high bioavailability, and a favorable adverse effects profile.…”
Section: Clinical Efficacy Of the 5-ht 1b/1d Receptor Agonistsmentioning
confidence: 99%
“…1) is a 5-hydroxytryptamine (5-HT1B/1D) receptor agonist, efficacious in the treatment of migraine. The mechanism of action of the (5-HT1B/1D) receptor agonist has been thoroughly studied [1][2][3][4] and leads to two main theories. Sumatriptan acts as a vasoconstrictor of dilated intracranial blood vessels and, also as an inhibitor of the pro-inflammatory neuropeptide release which leads to headache relief.…”
Section: Introductionmentioning
confidence: 99%
“…4 Though the premarketing experience failed to demonstrate its ischemic potential, we report on a case of ischemic colitis associated with the use of naratriptan. 5 This suggests that the development of ischemic colitis may be a class effect of the triptans.…”
mentioning
confidence: 98%